Australian tariff preferences for LDCs - P. J. Lloyd (Intereconomics, 1972)
In the course of the discussion of the tariff preferences granted by various developed nations to less developed countries (LDCs) it should be noted that it was Australla which first set up a comprising preference scheme. The author of this article outlines the scheme and appraises the Australlan experience.
Keywords: 330; Foreign Trade